Scotland's first farmers: new insights into early farming practices in North-west Europe. (October 2022) - Bishop, Rosie R.; Gröcke, Darren R.; Ralston, Ian; Clarke, David; Lee, Daniel H.J.; Shepherd, Alexandra; Thomas, Antonia S.; Rowley-Conwy, Peter A.; Church, Mike J.
Abstract: Abstract : Thirty years after the discovery of an Early Neolithic timber hall at Balbridie in Scotland was reported in Antiquity, new analysis of the site's archaeobotanical assemblage, featuring 20 000 cereal grains preserved when the building burnt down in the early fourth millennium BC, provides new insights into early farming practices. The results of stable isotope analyses of cereals from Balbridie, alongside archaeobotanical and stable isotope results from three other sites, indicate that while cereals were successfully cultivated in well-established plots without manuring at Balbridie, a variety of manuring strategies was implemented at the other sites. These differences reinforce the picture of variability in cultivation practices across Neolithic North-west Europe.